Tecnologia de sementes de jurema-de-embira (Mimosa ophthalmocentra Mart. ex Benth - Freitas, Narjara Walessa Nogueira de (Universidade Federal Rural do Semi-Árido, 2016)
The germination, as well as the expression of the effect of a seed lot, depends both on intrinsic factors of the seed (dormancy and speed of water absorption) as extrinsic factors (appropriate temperature, range suitable substrate, quantity and quality of water), being extremely important to know the factors that influence the germination of a given species. In this sense, four experiments were conducted with jurema-de-embira, in order to characterize morphologically fruits and seeds, evaluate the process of soaking seeds, set the best pre-germination treatment to overcome dormancy, determine appropriate procedures for the germination test and verify the effects of drought and salt stress on germination and early seedling development of jurema-de-embira under different temperatures. The experiments were conducted at the Seed Analysis Laboratory (LAS) of the Federal Rural University of the Semi-Arid (UFERSA). The statistical design was completely randomized (DIC). In experiment 1, for the characterization, we evaluated the biometric parameters of 100 fruits and 100 seed lots harvested in the years 2013 and 2014. For the characterization of the seed hydration, the process was carried out soaking curve of seed lots with and without lopping. We also evaluated nine pre-germinating treatments to overcome seed dormancy: control; cutting with scissors and escaficação with sandpaper 80, at the opposite end to the hilum; Hot water at 80 ° C for 3, 6 and 12 minutes and sulfuric acid (H2SO4) for 3, 6 and 12 minutes. In experiment 2, the substrates used were rolled paper, on paper, from vermiculite and sand, at temperatures of 25, 30 and 35 °C and alternated 20-30 °C, photoperiod of eight hours. In Experiment 3, we evaluated the osmotic potential of 0.0; -0.1; -0.2; -0.3; -0.4; -0.5 and -0.6 MPa at constant temperatures of 25, 30 and 35 ºC and alternated 20-30 °C. In the experiment 4, the evaluated salt concentrations were 0.0; 4.0; 8.0; 12.0; 16.0; 20.0; 24.0 and 28.0 dS m-1 under constant temperatures of 25, 30 and 35 °C and alternated 20-30 °C. The seeds of jurema-de-embira have low variation for biometric features and the larger variations occur from plant materials. Seed germination starts after 19 hours of imbibition, regardless of plant material. The scarification with sandpaper 80 or emerges with scissors at the opposite end to the hilum are the methods set out to overcome dormancy in seed jurema-of-embira. For the germination test in seed jurema-of-embira, the most favorable temperatures are 25 and 20-30 °C in the paper roll substrates and between sand. The water affects the germination of jurema-of-embira and early development of seedlings from the potential of -0.2 MPa, the most obvious effect in temperature of 35 °C; alternating temperature of 20-30 °C allows greater tolerance to drought stress. The effect of salinity varies with temperature, being more evident at the temperature of 35 °C. The jurema-of-embira is tolerant to salt stress and may be classified as a halophyte species
Seed technology jurema-of-embira (Mimosa ophthalmocentra Mart. ex Benth
Keywords: Mimosa - ophthalmocentra; Jurema-of-embira; Biometry; Mimosa - ophthalmocentra; Jurema-de-embira; Biometria; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA